Diabetes mellitus increases the risk of hepatocellular carcinoma in treatment-naïve chronic hepatitis C patients in China. Issue 13 (March 2017) - Li, Xu; Xu, Hongqin; Gao, Yang; Pan, Meng; Wang, Le; Gao, Pujun
Abstract : Abstract: We investigated the link between diabetes mellitus (DM) and hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC) risk in treatment-naïve chronic hepatitis C (CHC) patients in China. To examine the association between DM and HCC, we conducted a case–control study of 300 Chinese CHC patients with HCC, compared to an age- and sex-matched control group of 517 CHC patients not diagnosed with HCC. We found that DM was more prevalent in the HCC patient group (18.7%) than in the CHC-only patient group (10.8%). We conducted logistic regression analyses adjusting for demographics features and other HCC risk factors and found that DM increased the risk of HCC development nearly 2-fold [adjusted odds ratio (AOR), 95% confidence interval (95% CI), 1.80 (1.17–2.75)]. Meanwhile, the proportion of HCC patients and CHC-only patients with liver cirrhosis were 79.3% and 46.2%, respectively, yielding an AOR of 4.62 (95% CI, 3.31–6.46). Multivariate analyses comparing the risk of HCV-related HCC development in DM patients with and without liver cirrhosis revealed that the estimated AOR (95% CI) for those with liver cirrhosis was 5.60 (2.25–13.96). However, the HCC risk decreased significantly with a later age of diabetes onset (AOR [95% CI], 0.94 [0.89–0.99]). DM was associated with an increased risk for HCC development in treatment-naïve CHC patients in China. Furthermore, liver cirrhosis and an early DM diagnoses further increased the risks of HCC development in patients diagnosed with both CHC and DM.